2003
DOI: 10.1096/fj.02-0975fje
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning preserves connexin 43 phosphorylation during sustained ischemia in pig hearts in vivo

Abstract: During myocardial ischemia, connexin 43 (Cx43) is dephosphorylated in vitro, and the subsequent opening of gap junctions formed by two opposing Cx43 hexamers was suggested to propagate ischemia/reperfusion injury. Reduction of infarct size (IS) by ischemic preconditioning (IP) involves activation of protein kinase C (PKC) and p38 mitogen activated protein kinase (MAPK), both of which can phosphorylate Cx43. We now studied in anesthetized pigs whether IP impacts on Cx43 phosphorylation by measuring the density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 56 publications
7
152
1
3
Order By: Relevance
“…When cardiac tissue is immunoblotted for Cx43, only slower migrating "phosphorylated" isoforms are observed. Myocardial ischemia leads to Cx43 "dephosphorylation" (i.e., the loss of P1, P2, etc and gain of P0) and loss of localization from the intercalated disk, which likely contributes to contractile failure and arrhythmias (Beardslee et al, 2000;Schulz et al, 2003). We have shown that Cx43 localized to intercalated disks is phosphorylated at S325, S328 and/or S330 and that ischemia leads to loss of this phosphorylation and re-localization of the protein (Lampe et al, 2006).…”
Section: Introductionmentioning
confidence: 86%
“…When cardiac tissue is immunoblotted for Cx43, only slower migrating "phosphorylated" isoforms are observed. Myocardial ischemia leads to Cx43 "dephosphorylation" (i.e., the loss of P1, P2, etc and gain of P0) and loss of localization from the intercalated disk, which likely contributes to contractile failure and arrhythmias (Beardslee et al, 2000;Schulz et al, 2003). We have shown that Cx43 localized to intercalated disks is phosphorylated at S325, S328 and/or S330 and that ischemia leads to loss of this phosphorylation and re-localization of the protein (Lampe et al, 2006).…”
Section: Introductionmentioning
confidence: 86%
“…2) (Contreras et al, 2002). While Cx43 is phosphorylated under physiological conditions van Veen et al, 2001) and remains so in the first few minutes of ischemia , subsequent dephosphorylation of Cx43 occurs with increasing duration of myocardial ischemia (Beardslee et al, 2000;Jain et al, 2003;Jeyaraman et al, 2003;Miura et al, 2004;Schulz et al, 2003) a process that has been associated with the opening of unapposed Cx43Hc (John et al, 1999b;Li et al, 2001) which results in metabolic stress and cell death. Based on single Hc conductance measurements, it was suggested that opening of only 50 Hc is sufficient to drown the cell with Na + (John et al, 1999b).…”
Section: Unapposed Cx43hc Opening In Ischemia/reperfusion Injurymentioning
confidence: 99%
“…Cx43Hc dephosphorylation (Beardslee et al, 2000;Jain et al, 2003;Jeyaraman et al, 2003;Miura et al, 2004;Schulz et al, 2003) and opening (John et al, 1999b;Kondo et al, 2000;Shintani-Ishida et al, 2007) have been proposed as key mechanisms underlying cell injury in response to simulated ischemia in cardiomyocytes. Preservation of Cx43 phosphorylation by selective activation of the ɛPKC isoform occurs in response to ischemic pre- (Chou & Messing, 2005;Liu et al, 1999;Ytrehus et al, 1994) and postconditioning (Penna et al, 2006a;Philipp et al, 2006;Zatta et al, 2006), in which brief episodes of ischemia reduce the adverse effects of subsequent or preceding myocardial ischemia, respectively.…”
Section: Pkc Isoform Selective Modulation Of Cx43hcmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in cultured neonatal rat cardiomyocytes have identified multiple sites on Cx43 for phosphorylation by several kinases (22,37,47). Schultz et al (38) reported that colocalization of PKCα, p38MAPKα, and p38MAPKβ with Cx43 during ischemia increased only in preconditioned pig hearts and preserved phosphorylation of Cx43 during ischemia.…”
Section: Introductionmentioning
confidence: 99%